Let d represent number of days and n represent number of workers.
We have been given that when building a house, the number of days required to build varies inversely with with the number of workers.
We know that the equation
represents the relation where y is inversely proportional to x and k is the constant of proportionality.
So our required equation would be ![d=\frac{k}{n}](https://tex.z-dn.net/?f=d%3D%5Cfrac%7Bk%7D%7Bn%7D)
Upon substituting our given values, we will get:
![19=\frac{k}{35}](https://tex.z-dn.net/?f=19%3D%5Cfrac%7Bk%7D%7B35%7D)
![k=19\cdot 35](https://tex.z-dn.net/?f=k%3D19%5Ccdot%2035)
![k=665](https://tex.z-dn.net/?f=k%3D665)
Since constant of proportionality is 665, so our equation would be
.
To find the number of days it will take to build a similar house with 5 workers, we will substitute
in our equation as:
![d=\frac{665}{5}](https://tex.z-dn.net/?f=d%3D%5Cfrac%7B665%7D%7B5%7D)
![d=133](https://tex.z-dn.net/?f=d%3D133)
Therefore, it will take 133 days for 5 workers to build a similar house.
Answer:
∠x = 59°
Step-by-step explanation:
∠ECD = 52° because they are alternate angles and will be equal
∠x = 180° - 52° - 69° = 59° because the sum of the interior angles of a triangle = 180°
Answer:
shift the graph up 1 unit
Step-by-step explanation:
d is the vertical shift
+1 means we shift the graph up 1 unit
The completely factored expression of 2x^2 + 4x + 3xy + 6y is (2x + 3y)(x + 2)
<h3>How to factor the polynomial?</h3>
The expression is given as:
2x^2 + 4x + 3xy + 6y
Group the expression into two
[2x^2 + 4x] + [3xy + 6y]
Factor out each group
2x(x + 2) + 3y(x + 2)
Factor out x + 2
(2x + 3y)(x + 2)
Hence, the completely factored expression of 2x^2 + 4x + 3xy + 6y is (2x + 3y)(x + 2)
Read more about factored expression at:
brainly.com/question/723406
#SPJ1
Answer:
2x + 3 )(x + 2 )
Step-by-step explanation:
2x² + 7x + 6
Find two numbers multiplied together to get 6
and if you multiply one by 2, the answer is 7:
Tested:
6 & 1 but 6 · 2 + 1 = 13 or 6 + 2 · 1 = 8 No
2 & 3 and 2 · 2 + 3 = 7 Yes
2x² = 2x & x
all signs are positive
trinomial factoring ( )( )
( + )( + )
2 and 3 are the numbers to use (2x + 3 )(x + 2 ) or (2x + 2) (x + 3)
The largest number goes with the 2x.
Therefore (2x + 3 )(x + 2 )
Check 2x(x + 2) + 3(x + 2)
2x² + 4x + 3x + 6
2x² + 7x + 6 checked